Effect of microstructure on wear characteristics of spray cast al-si alloys - Raju K.; Harsha A.P.; Ojha S.N. (My University, 2025)
In the present study, the effect of microstructure on the wear characteristics of spray cast Al- 15Si and Al-20Si alloys has been investigated and compared with that of vertical axis centrifugal cast and chill cast alloys. The spray cast alloys have been subjected to Hot Isostatic Pressing for porosity reduction. HIPing has reduced the porosity in the spray cast Al-15Si and Al-20Si alloys from 19% to 8% and 19% to 2% respectively. The microstructures of spray cast alloys consisted of finely divided globular shaped Si particles with sizes varying from 2-10 μm. The Si particles have been distributed uniformly throughout the Al matrix. On the contrary coarse and segregated microstructures have been observed in vertical axis centrifugal cast and chill cast alloys. The sizes of primary and eutectic Si in vertical axis centrifugal cast alloys are smaller than that in chill cast alloys. The wear rates are the lowest for spray cast alloys and highest for chill cast alloys over a wide range of sliding velocity. The reasons for better wear resistance of spray cast alloys have been discussed in the light of the microstructural features evolved during spray casting. © (2012) Trans Tech Publications.